CTNI-53. RADIATION TREATMENT VOLUMES BEFORE AND AFTER BRAF/MEK THERAPY IN NEWLY DIAGNOSED PAPILLARY CRANIOPHARYNGIOMAS: A CORRELATIVE ANALYSIS OF THE ALLIANCE A071601 PHASE II TRIAL. (12th November 2021) - Shih, Helen; Tabrizi, Shervin; Kabat, Brian; Twohy, Erin; Geyer, Susan; Vora, Shivangi; Gerstner, Elizabeth; Kaufmann, Timothy; Ruff, Michael; Reardon, David; Cohen, Adam; Bota, Daniela; et al.
Abstract: PURPOSE: Standard of care for craniopharyngiomas is surgery with or without radiotherapy (RT). Cohort A of Alliance A071601 evaluated the efficacy of BRAF/MEK inhibition with vemurafenib/cobimetinib in patients with previously untreated papillary craniopharyngiomas (PCP), which carry the BRAF V600E mutation. Cohort B is currently enrolling patients with recurrence after RT. In a correlative analysis, we examined changes in RT volumes after BRAF/MEK therapy in Cohort A. METHODS: Previously unirradiated patients with BRAF-mutated PCP were treated with vemurafenib/cobimetinib. Sixteen patients had scans available before starting vemurafenib/cobimetinib ("pre-therapy") and after completing therapy ("post-therapy"). Two patients went off study treatment after 8 and 9 days due to side-effects and were excluded for this analysis. Gross target volumes (GTV) were contoured on pre-therapy and post-therapy scans. On post-therapy scans, an additional target comprising gross disease and at-risk regions for microscopic residual disease (GTV-micro) was defined and considered the treatment volume. Clinical target volume (CTV) was a 5-mm uniform expansion on pre-therapy GTV and post-therapy GTV-micro. Volumes were independently reviewed by two radiation oncologists. Changes in volumes from pre- versus post-therapy were compared using the Wilcoxon signed rank test. RESULTS: In 14 patients evaluated, 57% were female and median age at enrollment was 49.5 years (range 33-83). Median time on treatment was 8.9 months (range 4.0-18.0). Median GTV pre-therapy was 3.8 mL (range 0.2-23.4) versus 0.3 mL (range 0.0-3.2) post-therapy (p=0.0001) and 1.7 mL (range 0.1-8.0) post-therapy GTV-micro (p=0.0001). Median CTV pre-therapy was 13.7 mL (range 2.8-51.8) versus 9.1 mL (range 2.2-27.5) post-therapy (p=0.0001). All tumors abutted the optic chiasm pre-therapy, only 6 did post-therapy. CONCLUSIONS: Vemurafenib/cobimetinib resulted in smaller RT volumes. BRAF/MEK inhibitors could reduce RT volumes and spare dose to surrounding normal structures. Enrollment to Cohort B of Alliance A071601 should be considered for patients with recurrent tumors after RT. SUPPORT: https://acknowledgments.alliancefound.org